Analisis Dinamik Model Matematika Penyebaran Penyakit HIV/AIDS dengan Edukasi Dan Art Treatment - Syafii, Mohamad; Sabran, La Ode; Rianjaya, Ilham Dangu (MES: Journal of Mathematics Education and Science, 2023)
Mathematical models are often used to describe phenomena in the field of biology, such as the spread of infectious diseases, one of which is HIV/AIDS. The prevention of HIV/AIDS is through education on the dangers of HIV/AIDS, and ART treatment for HIV positive individuals to increase immunity. The purpose of this study is to analyze the dynamic mathematical model of the transmission of HIV/AIDS with ART treatment and education. This research is a literature study. This study develops the SITA model, by including compartments of susceptible individuals who are aware of the spread of HIV/AIDS and add several parameters to the model. Based on the mathematical model used, two equilibrium points are obtained, namely the disease-free equilibrium point and the endemic equilibrium point, the basic reproduction number and stability analysis around the stability point. Based on the data used, a simulation of the transmission of HIV/AIDS was obtained at both equilibrium points. The stability analysis shows that the disease-free equilibrium point is locally asymptotically stable if R01.